A Voice for Maria Favela An Adventure in Creative Literacy - Leal, Antonio (Radical Politics and Education, 2022)
This open access book, originally published in Portuguese in 1988 and now available in English for the first time, describes the Brazilian educator, Antonio Leal's, experiences teaching so-called "unteachable" children in Rio de Janeiro's favelas. A Voice for Maria Favela tells the story of how Leal considers what the children bring to the class, gradually engaging them in developing a narrative about Maria Favela, a single mother and housemaid. Leal uses the sounds within the story to draw out the students' abilities to see enunciation and articulation as a process of becoming literatized. A contemporary and admirer of Paulo Freire, Leal nevertheless recognised that his students' needs could not be theorized along Freirean lines of oppressor/oppressed. He devised an emancipatory approach that is more focussed on the individual child and their capacity for self-expression than those often found in critical pedagogy. The book puts forward a unique type of radical pedagogy and philosophy of education, developed through direct classroom observation. The book includes a substantial introduction written by the translator Alexis Gibbs (University of Winchester, UK) and preface by Inny Accioly (Fluminense Federal University, Brazil). The eBook editions of this book are available open access under a CC BY-NC-ND 4.0 licence on bloomsburycollections.com.